PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI KONSUMEN PRODUK KOSMETIK WARDAH (Studi Kasus Konsumen Matahari Department Store Mall Ska Pekanbaru) - Rizki, Rahmad; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the effect of product quality and price on consumer buying (consumer case study Matahari Department Store Mall Ska Pekanbaru). Product Quality as variable (X1), Price as variable (X2) and Consumer buying interest as variable (Y). The method in this research is quantitative with SPSS program, where the sample used is Matahari Department Store Mall Ska Pekanbaru that is as much as 99 respondents. In accordance with opinion (Roscoe, 2009) that the appropriate size in the study is 30 to 500. That number can already represent the population. Technique of collecting data through questionnaire. The results of analysis using the validity test, test reliability, test determination, simple linear regression test, multiple linear regression test, t test and F test. The results showed that product quality partially influence consumer buying interest, price partially influence consumer buying interest, so product quality and price simultaneously have a positive effect on consumer buying Matahari Department Store Mall Ska Pekanbaru. Keywords: Product Quality Price and Consumer Buying